Exploring User Interface Constraints for Reading and Writing - Joshi, Nikhita (University of Waterloo, 2025)
Constraints are fundamental to human-centred design. Although by definition, constraints "limit" or "restrict" the capability of software, when designed correctly, they can have enabling characteristics as well. I sought to understand how user interface constraints can positively affect user outcomes, in ways that go beyond traditional goals of error-proofing. Drawing from different theories in psychology, this dissertation presents four projects that study different types of user interface constraints while reading and writing. First, in a passive reading context, I evaluate the effects of two commonly-used document navigation techniques on reading comprehension: scrolling, where the reader has complete control over the viewport position; and pagination, where the viewport is restricted to specific locations. Second, in an active reading context, I propose limiting the number of words that can be highlighted in document reader software to improve reading comprehension scores. Third, when writing with large language models, I propose requiring users to write longer prompts so they feel more psychological ownership towards the generated output, and design interaction techniques to nudge users to write longer prompts. Finally, when prompting large language models to learn more about documents, I propose restricting where prompting can occur by requiring it to be anchored to specific text in the document and design new commenting techniques with different requirements that must be satisfied to finalize the comment. Overall, this dissertation demonstrates the potential of user interfaces and interaction techniques that purposely constrain users. Through several controlled experiments, my findings suggest that user interface constraints may not be effective for certain activities, like when passively reading, but when actively reading and writing with large language models, they can often encourage positive user outcomes, like improved reading comprehension and psychological ownership. However, designing interaction techniques that leverage 'soft' constraints is challenging, and such interaction techniques do not always nudge users. Together, this dissertation contributes knowledge on the effectiveness of non-error-proofing constraints when reading and writing, and interaction techniques that can be integrated into current reading and writing interfaces.
Keywords: human-computer interaction; human-AI interaction; user interface constraints